Paraspeckles - Fox, A. H.; Lamond, A. I. (Cold Spring Harbor perspectives in biology, 2010)
Paraspeckles are a relatively new class of subnuclear bodies found in the interchromatin space of mammalian cells. They are RNA-protein structures formed by the interaction between a long nonprotein-coding RNA species, NEAT1/Men epsilon/beta, and members of the DBHS (Drosophila Behavior Human Splicing) family of proteins: P54NRB/NONO, PSPC1, and PSF/SFPQ. Paraspeckles are critical to the control of gene expression through the nuclear retention of RNA containing double-stranded RNA regions that have been subject to adenosine-to-inosine editing. Through this mechanism paraspeckles and their components may ultimately have a role in controlling gene expression during many cellular processes including differentiation, viral infection, and stress responses.